Fe₂O₃ PARTICLES AS PRECURSORS FOR α”-Fe₁₆N₂ PHASE SYNTHESIS - ONE, R. A.; BORTNIC, R.; MICAN, S.; BARBU-TUDORAN, Lucian; POP, V. (Studia Universitatis Babeș-Bolyai Physica, 2016)
In this work we investigate the structural properties and microstructure of Fe2O3 particles synthesized using the sol-gel method. Differential thermal and thermogravimetric analysis showed that the organic matrix is completely burned off at temperatures higher than 520 °C. The sample annealed at 550 °C for 12 h contained only the Fe2O3 phase. The obtained hematite particles are micrometer sized and have an elongated shape. Taking into account the cheap and available sol-gel precursors, the possibility of using these particles in α”-Fe16N2 synthesis is discussed.